Decline in the DPRK's Anthracite Export to China: Causes and Implications - Jongkyu Lee (Korea Development Institute (KDI), 2015)
North Korea's anthracite export to China, which represents more than 40% of its total exports, is experiencing fall outs from a downturn in export unit prices, China's dwindling steel industry, the Chinese government's restructuring plans for the steel industry, and strengthened environmental regulations. The time has come for North Korea to reshape its external trade structure which has persevered since the May 24 measures. In recognition of this, the South Korean government now needs to consider flexible North Korea policies which will provide incentives for the North Korean economy. - North Korea's anthracite export to China has greatly contributed to the stabilization of the North Korean economy. - Analysis into the determinants of North Korea's anthracite export to China will offer foresight into the changes in the North Korean economy albeit indirectly. - Drop in North Korea's anthracite export to China in 2014 caused a fall in its overall trade with the country. - Steel makers and ceramic manufacturers and Shandong Province, Liaoning Province, Hebei Province, and Jiangsu Province have been the main consumers of North Korean anthracite. - Price of North Korean anthracite fell to US73.4 per ton in 2014 from US102 in 2011, mainly influenced by the slump in the world's steel industry and a sluggish Chinese economy. - Fall in unit price was a common factor of reduced export scale for major destinations. - The monthly statistical sums of the export of the 'North Korea' category and the 'Other unspecified Asian countries' category of China's General Administration of Customs generally correlate with those of the UN's annual trade statistics. - Regression analysis showed that local steel production in China has the biggest impact on North Korea's anthracite export. - The Chinese government's policy plans imply more unfavorable environments for North Korea's anthracite export. - North Korea is expected to diversify its external trade relations. Thus, the South Korean government needs to prepare more flexible North Korea policies.
Keywords: 330